Polymeric Micelles for Breast Cancer Therapy: Recent Updates, Clinical Translation and Regulatory Considerations - Vijayabhaskarreddy Junnuthula; Praveen Kolimi; Dinesh Nyavanandi; Sunitha Sampathi; Lalitkumar K. Vora; Sathish Dyawanapelly (Pharmaceutics, 2022)
With the growing burden of cancer, parallel advancements in anticancer nanotechnological solutions have been witnessed. Among the different types of cancers, breast cancer accounts for approximately 25% and leads to 15% of deaths. Nanomedicine and its allied fields of material science have revolutionized the science of medicine in the 21st century. Novel treatments have paved the way for improved drug delivery systems that have better efficacy and reduced adverse effects. A variety of nanoformulations using lipids, polymers, inorganic, and peptide-based nanomedicines with various functionalities are being synthesized. Thus, elaborate knowledge of these intelligent nanomedicines for highly promising drug delivery systems is of prime importance. Polymeric micelles (PMs) are generally easy to prepare with good solubilization properties; hence, they appear to be an attractive alternative over the other nanosystems. Although an overall perspective of PM systems has been presented in recent reviews, a brief discussion has been provided on PMs for breast cancer. This review provides a discussion of the state-of-the-art PMs together with the most recent advances in this field. Furthermore, special emphasis is placed on regulatory guidelines, clinical translation potential, and future aspects of the use of PMs in breast cancer treatment. The recent developments in micelle formulations look promising, with regulatory guidelines that are now more clearly defined; hence, we anticipate early clinical translation in the near future.